(3GdJLQHI GdjGHGfjI aj GdGOGQI hGdJfXje (B:s (3GdOYGFe GdGSGSjI hebheGJ GdfLGM (B/s - (3GHh bMa, YHO GdSdGes ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 1998)
(3aj gPG GdcJGH (B: (3GdfXGe GdGOGQi hOYGFeI Ydi eSJhi GdOhdI GdfXGe GdGOGQj(B: (3GdNUGFU h GdSeGJ h GdOYGFe GdGSGSjI h GdGSJKeGQGJ , GdedGeM h GdeMGhQ GdGSGSjI dfXe GdGOGQI h GdJfXje, GdGfJGLjI h GSHGH GdfLGM aj GdeUGfY h GdTQcGJ, HYV GdeeGQSGJ GdGOGQjIs
(3HjHdjhZQGajG (B: (3GdLRA GdGhd U (B.59 (3; GdLRA GdKGfj U(B. 134s
Keywords: (3GdGOGQIs